2019
DOI: 10.1186/s12939-019-1025-z
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and explaining changing patterns of inequality in institutional deliveries between urban and rural women in Ghana: a decomposition analysis

Abstract: Background Despite recent progress in improving access to maternal health services, the utilization of these services remains inequitable among women in developing countries, and rural women are particularly disadvantaged. This study sought to measure i) disparities in the rates of institutional births between rural and urban women in Ghana, ii) the extent to which existing disparities are due to differences in the distribution of the determinants of institutional delivery between rural and urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 18 publications
(18 reference statements)
4
24
0
1
Order By: Relevance
“…This was also true for ANC follow up, presence of media access, single and grand parity. This finding is also supported by results in India [10] in Ghana [11] and in 80 low and middle-income countries study result [33]. In addition, husband secondary and higher education and age at childbirth were all important contributors to close the urban-rural gap of institutional delivery in Ethiopia.…”
Section: Plos Onesupporting
confidence: 66%
See 2 more Smart Citations
“…This was also true for ANC follow up, presence of media access, single and grand parity. This finding is also supported by results in India [10] in Ghana [11] and in 80 low and middle-income countries study result [33]. In addition, husband secondary and higher education and age at childbirth were all important contributors to close the urban-rural gap of institutional delivery in Ethiopia.…”
Section: Plos Onesupporting
confidence: 66%
“…There is considerable evidence that rural women gave home delivery compared to their urban counterparts [4,5,9,10]. For instance, decomposition analysis unfolded that urban residences in India and Ghana positively contributed to the facility delivery inequalities [10,11]. Another study conducted in Ethiopia [12][13][14], Guinea-Bissau [15], and Malawi [16] also showed similar findings.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Evidence from a crosscountry study performed in 18 Sub-Saharan countries has also revealed that wealth was the single most important driver of inequality in maternal healthcare utilization [60]. Prior studies [20,41,61,62] on related maternal health issues in Ethiopia and other developing countries also documented similar findings. Wealth status could affect birth interval of women through its effect on accessing family planning information and services.…”
Section: Discussionmentioning
confidence: 70%
“…47 Legally, maternal health services are free of charge in Ethiopia; 48 however, transportation and other opportunity costs, such as time spent on travel for the woman and accompanying families, are known to deter a woman's use of a health facility. 43,44,49 Interventions targeting poor women, such as maternity waiting homes, cash assistance, conditional cash transfer, and voucher and equity funds, are known to help increase the rate of facility births. 37,[50][51][52] A single-year increase in a woman's age at first childbirth was significantly associated with facility birth.…”
Section: Discussionmentioning
confidence: 99%